Neorrevisionismo e manutenção da sociedade internacional: o papel da Rússia como grande potência na dinâmica de segurança contemporânea - Cassarotti, Luis Francisco Calegari (2021)
The maintenance of the normative impetus of the Cold War on the part of the USA and the countries of Western Europe puts Russia aside, which sees its historical interest in assuming rights and fulfilling the duties and responsibilities of a great power curtailed. The country finds itself in a kind of strategic impasse that denies both the possibility of partnership and the desire for an active voice in world politics. As a symptom of this state of relations, Russian leaders assume an emphatic posture of defiance and resistance, usually embodied as a fierce defense of the basic principles of interstate relations. Understanding the purpose and effects of this phenomenon is essential to glimpse the meaning of the transformations that lie ahead in contemporary international society. In this regard, this work calls into action whether such a position is consistent with the Russian State's attempt to assert itself as a member of the club of great powers. To this end, the study articulates the theoretical precepts of the English School for the definition of the analysis parameters and the methodological construction. We used the historical method to evaluate Russia's role in the current international society's balance of power, its secular interest in assuming great power duties, and whether it achieves such functions. The investigation firstly included a reconstitution of the Russian history within the international society and, secondly, a more in-depth analysis of its role in the following three cases: the construction of the Nuclear Treaty with Iran, the Ukrainian Crisis, and the Syrian Conflicts. In conclusion, the findings of this study suggest that the provocative insertion of Russia in world politics is consistent with a classification of great power, confirming the work's hypothesis.